2017
DOI: 10.1021/acs.jpcc.7b10265
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Recognition of Ice by Fully Flexible Molecules

Abstract: Cold acclimatized organisms produce antifreeze proteins that prevent ice growth and recrystallization at subfreezing conditions. Flatness and rigidity of the ice-binding sites of antifreeze proteins are considered key for their recognition of ice. However, the most potent synthetic ice recrystallization inhibitor (IRI) found to date is poly(vinyl alcohol) (PVA), a fully flexible molecule. The ability to tune the architecture and functionalization of PVA makes it a promising candidate to replace antifreeze prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
128
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(134 citation statements)
references
References 74 publications
4
128
2
Order By: Relevance
“…[33] Hyperactive AFPs, which display a larger thermal hysteresis gap can also bind the basal face. [34,35] Experimental and modeling evidence supports PVA's unique activity being due to its hydroxyls precisely matching the spacing on the prism plane of ice, and a balance of enthalpy/entropy compensation leads to increased affinity and hence inhibition [36][37][38] due to a multivalent or "zipper" effect ( Figure 2C). This also explains why many other polyols fail to inhibit growth as they do not have this extended stretch of hydroxyls with precise spacing, with a range of glycopolymers or carbohydrates (see Supporting Information) showing very little activity.…”
Section: Proteins and Polymers Which Bind Icementioning
confidence: 99%
See 2 more Smart Citations
“…[33] Hyperactive AFPs, which display a larger thermal hysteresis gap can also bind the basal face. [34,35] Experimental and modeling evidence supports PVA's unique activity being due to its hydroxyls precisely matching the spacing on the prism plane of ice, and a balance of enthalpy/entropy compensation leads to increased affinity and hence inhibition [36][37][38] due to a multivalent or "zipper" effect ( Figure 2C). This also explains why many other polyols fail to inhibit growth as they do not have this extended stretch of hydroxyls with precise spacing, with a range of glycopolymers or carbohydrates (see Supporting Information) showing very little activity.…”
Section: Proteins and Polymers Which Bind Icementioning
confidence: 99%
“…Polymer chain architecture has also shown to be important, with three‐arm PVA demonstrating IRI activity equal to that of a linear polymer the same length as two of the arms . It has been suggested that this is because of the inability of the third arm to effectively bind a basal plane of ice, as the other two arms (binding in a linear fashion) confine the third …”
Section: Proteins and Polymers Which Bind Icementioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent efficiency of proteins and alcohol monolayers indicates that the IBS does not need to be amphiphilic to bind strongly to ice. (3,16,32) INP width limits their ice nucleation temperature.…”
mentioning
confidence: 99%
“…Molinero and coworkers explore this tantalizing suggestion in a series of recent articles (5,20,21). In ref.…”
mentioning
confidence: 99%